Oral microbial profiles of extrinsic black tooth stain in primary dentition: A literature review - Xue Dong; Weijin Zhao; Sha Ma; Ximeng Li; Guiding Li; Shinan Zhang (Elsevier, 2024)
The extrinsic black tooth stain (EBS) is commonly found in primary dentition. Patients cannot clean the EBS; this can only be done by professional scaling and debridement. It also has a tendency to reform, which significantly compromises children's aesthetics and even affects their quality of life. However, there is no conclusive evidence on the etiology of the EBS. The associations between the EBS and related oral microbial features is one of the research hot topics. No literature review summarized these research progresses in this area. Therefore, we reviewed the literature on the microbiology of the EBS since 1931 and reported as the following 5 aspects: molecular biotechnology, morphological structure and physiochemical characteristics, microbial etiology hypothesis and core microbial characteristics. The EBS is a special dental plaque mainly composed of Gram-positive bacilli and cocci with scattered calcium deposits that acquired salivary pellicle activates. Early studies showed that the Actinomyces was the main pathogenic bacteria. With advances in biological research techniques, the 'core microbiome' was proposed. The potential pathogenic genera were Actinomyces, Prevotella nigrescens, Pseudotropinibacterium, Leptotrichia, Neisseria and Rothia. However, the pathogenic species of the above genera were still unclear. Currently, it is believed that the EBS consists of iron compounds or black substances that oral bacterial metabolism produces or that the bacterial metabolites formed after chemical reactions in the micro-ecological environment.